STRATEGI BAURAN PEMASARAN USAHA TANI KOPI ROBUSTA MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS (AHP) (Studi di Kecamatan Rajadesa, Kabupaten Ciamis) - Mochamad Arief Rizki Mauladi; Ane Novianty; Anisa Puspitasari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Ciamis Regency is one of the coffee-producing areas in West Java that has good potency for the development of local coffee. Suitable land conditions and the development of coffee shops in the downstream sector provide hope for farmers to produce coffee that is acceptable to a growing market. However, so far coffee marketing has only been done conventionally through intermediary traders which have been carried out for generations without the right marketing strategy following the conditions faced by farmers. This study aims to determine the 4P marketing mix strategy according to the conditions faced by farmers. The results of the study show that in the product marketing mix, the development of human resource capabilities is prioritized because good human resources can facilitate farming businesses to produce quality coffee beans. Then in the price marketing mix, coffee quality is prioritized because it is the most determining factor in the selling price of coffee. Then in the place marketing mix, distance from consumers is a priority factor because it can make coffee distribution more efficient. Meanwhile, in the promotion marketing mix, the coffee promotion event factor is prioritized because it can encourage local coffee to be better known by the public.